LA CORRESPONSABILIDAD FAMILIAR EN EL CUIDADO Y DESARROLLO PERSONAL DE LAS PERSONAS CON DISCAPACIDAD FÍSICA PERTENECIENTES AL CENTRO DE SALUD N°2 HUGO GUILLERMO GONZÁLEZ DE LA CIUDAD DE LOJA Y EL ROL DEL TRABAJADOR SOCIAL - González Ulloa, Nuria Priscila (2019)
This research is part of FAMILY RESPONSIBILITY IN THE CARE AND PERSONAL DEVELOPMENT OF PERSONS WITH PHYSICAL DISABILITIES BELONGING TO THE HEALTH CENTER No. 2 HUGO GUILLERMO GONZÁLEZ DE LA CIUDAD DE LOJA AND THE ROLE OF THE SOCIAL WORKER is based on the study family, people with physical disabilities and social work with the purpose of providing a proposal for social intervention that allows strengthening family participation and improving their quality of life. The specific objectives that were raised allowed us to carry out a situational diagnosis of family co-responsibility as a determining axis in the care and personal development of people with physical disabilities. The causes that caused the lack of empathic participation and responsibility in families and how are they identified were identified. actions directly influence the care and personal development of people with physical disabilities and sole proprietors, in the same way, the information collected was analyzed and the design of a proposal for social intervention that responds to the general objective set in the investigation. In order to carry out the field work, the scientific method was mainly used and as a complement to the inductive, deductive, analytical, descriptive and bibliographic method, as well as techniques such as observation, interview, focus groups and the zarit test themselves. were extremely necessary for the collection of information regarding the co-responsibility in the care and personal development of people with physical disabilities always directed to comply with the objectives set in the investigation process. The results obtained emphasize the lack of family co-responsibility in the care and personal development of the person with physical disability, which causes a single family member to - 5 - suffer from problems of stress, depression, low self-esteem, etc., due to overload. that they present, which influences the character and personal development of the person with physical disability in that it brings consequences such as aggressiveness towards the caregiver, low self-esteem, low autonomy, depression which significantly affects the family both personally as a whole, based on the interpersonal relationships that must be maintained within the family and their social context. The role played by the Social Worker is of great importance in improving equitable participation and relationship between the family and the person with physical disabilities, so a proposal for social intervention was created and recommended to the Health Center No. 2 Hugo Guillermo González and the professionals in charge of the disability group apply the activities of the intervention proposal.